(untitled) (International Journal of Computer Science and Engineering, 2026)
Addressing the escalating global burden of long-term care requires a fundamental re-evaluation of how macroeconomic institutional structures actively shape micro-level clinical trajectories. This study investigates the institutional variance in standardized pathways for chronic disease and rehabilitation management across distinct healthcare models, utilizing a multidimensional comparative framework that integrates financing mechanisms, gatekeeping efficiency, and provider payment incentives. By critically examining the operational friction observed during our comparative matrix evaluation, particularly regarding the non-linear, often disrupted transitions between acute hospital interventions and community-based step-down rehabilitation, we delineate how fragmented institutional governance can inadvertently impede the continuity of care. The proposed optimization framework introduces a longitudinal, value-based integrated care pathway tailored specifically to transitional economic contexts. While the empirical boundaries of this research are to some extent constrained by regional data heterogeneities and evolving digital health infrastructures, the structural insights obtained strongly suggest that bridging the gap between specialized clinical care and primary health services depends heavily on systemic payment re-alignments. Considering the complex socio-political factors governing healthcare reforms, further research is undoubtedly needed to validate the scalability of these standardized pathways across diverse socio-economic landscapes, thereby leaving the long-term operational dynamics open to continuous empirical scrutiny.